miR-223 alleviates DSS-induced colitis by prompting macrophage M2 polarization through PPAR-γ/FOXO1 signaling - Zhang, Juanjuan; Wang, Lixin; Shen, Yingye; Qian, Xiaoli; Wang, Zhiming; Wang, Chenyang (Frontiers in Immunology, 2025)
BackgroundMacrophage polarization represents a promising therapeutic target for inflammatory bowel disease (IBD). This study investigates the role of miRNA-223 (miR-223) in dextran sodium sulfate (DSS)-induced colitis and its regulation of macrophage polarization.MethodsMale C57BL/6 mice were assigned to four groups: Wild-type (WT) control, DSS-treated group (DSS), DSS+miR-223 agomir (DSS+A), and DSS+ miR-223 agomir negative control (DSS+NC). Colitis was induced with 2.5% DSS for 7 days; miR-223 agomir or NC was administered intraperitoneally on days 2–4. We evaluated disease activity index (DAI), colonic inflammation, and the expression of inflammatory mediators, peroxisome proliferator-activated receptor gamma (PPAR-γ) and forkhead box transcription factor O1 (FOXO1). ResultsHistopathological analysis showed that miR-223 agomir significantly attenuated DSS-induced colon damage. Proinflammatory cytokines (TNF-α, IL-1β, IL-6) increased in DSS mice, while anti-inflammatory IL-10 decreased—trends reversed by miR-223 supplementation at mRNA/protein levels. Mechanistically, DSS elevated M1 macrophage marker iNOS and FOXO1 but reduced M2 marker Arg-1 and PPAR-γ. miR-223 agomir suppressed M1 polarization while enhancing M2 polarization by downregulating FOXO1 and upregulating PPAR-γ. ConclusionWe identify a novel dual-regulatory mechanism wherein miR-223 ameliorates colitis by shifting macrophage polarization from M1 to M2 via concurrent FOXO1 suppression and PPAR-γ activation. These findings establish a mechanistic basis for miR-223 supplementation as a novel IBD therapeutic strategy.